Prevalence of anxiety disorder and its association with BMI: an analysis of women’s experiences in Bangladesh using BDHS-2022 data - Farhana Afrin Duty; Md. Habibur Rahman; Nahid Salma (BMC Public Health)
Abstract Background Anxiety disorders are a significant and growing public health concern, impacting individuals’ daily lives and professional development. Women exhibit higher rates compared to men. Changes in body mass index (BMI) can affect the mental health of an individual. However, the relationship between BMI and anxiety is unclear. The purpose of this study was to investigate the association between BMI and anxiety disorder. Methods BDHS 2022 data were used. Binary logistic regression, restricted cubic spline analysis (RCS), and subgroup analyzes were performed to explore the relationship between BMI and anxiety disorder. Results The prevalence of anxiety disorders among ever-married women was approximately twenty one percent. A non-linear, U-shaped relationship between BMI and anxiety disorder was observed, with the lowest risk at a BMI of 22.78 kilograms per square meter. Obesity, as well as underweight, increased the risk of anxiety among the participants, especially in subgroups of participants who were older adults, less educated, lower wealth status, greater age at marriage, and longer cohabitation. For older women, with the lowest risk at a BMI of 25.6 kilograms per square meter, being slightly overweight might serve as a psychological buffer against anxiety. The highest prevalence rate was in formerly married women as well as in the women in the Rangpur division. Conclusion This study identified a significant association between BMI and anxiety disorder, revealing a U-shaped relationship where both underweight and obesity were correlated with higher odds of anxiety disorder. Although the results indicate that maintaining a healthy BMI could be associated with a decrease in anxiety levels, the cross-sectional nature of the study prevents establishing a causal relationship. This implies that BMI and anxiety may be correlated, but one does not necessarily cause the other. Future longitudinal studies are needed to explore potential causal mechanisms. The observed association highlights the importance of considering body weight extremes in mental health interventions. These findings underscore the need for integrated public health strategies that address both mental health and nutritional well-being among ever-married women in Bangladesh.